Aplicação da metodologia seis sigma em uma empresa de médio porte do setor têxtil - Feitor, Carlos David Cequeira (2008)
The Six Sigma methodology has received considerable attention in the last two decades. This is due to its great potencial to reduce processes variability, through the use of accurate data, facts and statistical techniques. The methodology seeks to improve the quality of products and services, maximizing the company s financial performance. Specifically, its implementation and results in medium-sized textile enterprises is unknow, although there are signs that the methodology can be applied with success. Considering this scenario, the goal of this research is to describe the application of the Six Sigma methodology in a médium-sized textile company specialized in the production of male shirts in the satate of Rio Grande do Norte, Brazil. First, we present a literature review, seeking to highlight the themes of quality, Six Sigma and its methodology for improvement. Then, we show the implementation of the project selected, depicting the steps and procedures that must be performed. The results confirm the efficiency of Six Sigma in providing significant gains to companies. It is observed substantial improvements in the speed of product development and the flexibility of the parts produced, reducing the process lead time from 12.5 to 6.2 days, which means a performance improvement of over 50%. This leads also to cultural and behaviour change, creating motivation for implementation of new projects and a continuous search for knowledge